From ESG Performance to Social Welfare: Financial Inclusion as a Development Pathway in Indonesian Islamic Banking - Maulidizen, Ahmad; Yuwono, Imam; Rizapoor, Habiburrahman (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the role of Environmental, Social, and Governance (ESG) performance in Indonesian Islamic banking and its implications for financial inclusion and socio-economic welfare. The increasing global focus on sustainable finance encourages Islamic banks to integrate ESG principles aligned with Sharia values and Maqasid al-Shariah. This study employs a qualitative approach using content analysis methods. Data were collected from academic journals, institutional reports, policy documents, and sustainability reports of Islamic banks. The findings indicate that ESG practices contribute significantly to expanding financial inclusion, particularly for underserved communities, while supporting socio-economic welfare through poverty reduction, equitable growth, and responsible financing. Financial inclusion acts as a mediating mechanism linking ESG initiatives to welfare improvement through economic empowerment. The novelty of this study lies in its integrative conceptual framework connecting ESG dimensions with Maqasid al-Shariah principles, thereby providing a holistic perspective on sustainable Islamic finance and ethical economic development